Biomechanical compensations during a stand-to-sit maneuver using transfemoral osseointegrated prostheses: A case series - Gaffney, Brecca M.M.; Vandenberg, Nicholas W.; Davis-Wilson, Hope C.; Christiansen, Cory L.; Roda, Galen F.; Schneider, Gary; Johnson, Tony; Stoneback, Jason W. (Clinical biomechanics (Bristol), 2022)
Patients with transfemoral amputation and socket prostheses are at a heightened risk of developing musculoskeletal overuse injuries, commonly due to altered joint biomechanics. Osseointegrated prostheses, which involve direct anchorage of the prosthesis to the residual limb through a bone anchored prosthesis, are a novel alternative to sockets yet their biomechanical effect is largely unknown. Four patients scheduled to undergo unilateral transfemoral prosthesis osseointegration completed two data collections (baseline with socket prosthesis and 12-months after prosthesis osseointegration) in which whole-body kinematics and ground reaction forces were collected during stand-to-sit tasks. Trunk, pelvis, and hip kinematics, and the surrounding muscle forces, were calculated using subject-specific musculoskeletal models developed in OpenSim. Peak joint angles and muscle forces were compared between timepoints using Cohen's d effect sizes. Compared to baseline with socket prostheses, patients with osseointegrated prostheses demonstrated reduced lateral trunk bending (d = 1.46), pelvic obliquity (d = 1.09), and rotation (d = 1.77) toward the amputated limb during the stand to sit task. This was accompanied by increased amputated limb hip flexor, abductor, and rotator muscle forces (d> > 0.8). Improved lumbopelvic movement patterns and stabilizing muscle forces when using an osseointegrated prosthesis indicate that this novel prosthesis type likely reduces the risk of the development and/or progression of overuse injuries, such as low back pain and osteoarthritis. We attribute the increased muscle hip muscle forces to the increased load transmission between the osseointegrated prosthesis and residual limb, which allows a greater eccentric ability of the amputated limb to control lowering during the stand-to-sit task. •Socket prostheses change joint biomechanics and increase the risk of overuse injury.•Osseointegrated prostheses normalize lumbopelvic biomechanics during sitting tasks.•Osseointegrated prostheses likely reduce the risk of joint overuse injury.